Musical Perceptions - Aiello, Rita; Sloboda, John A. (Oxford Oxford University Press, 1994)
Musical Perceptions is a much-needed text that introduces students of both music and psychology to the study of music perception and cognition. Because the book aims to foster a closer interaction between research in the science and the art of music, both psychologists and musicians contribute chapters on a wide range of topics, including the philosophy of music; research in musical performance; perception of melody, tonality, and rhythm; pedagogical issues; language and music; and neural networks. With their unique ability to introduce musical and psychological concepts to first-time students in the area, Rita Aiello and John Sloboda have edited a volume that will be popular with undergraduate and graduate students taking courses in the perception, psychology, and aesthetics of music. They have prefaced each chapter with an introduction to the chapter's research. This book will also be useful to cognitive and physiological psychologists and music theorists interested in music perception.
Keywords: Music psychology